Salvadora oleoides (Family: Salvadoraceae) – A New Larval Host Plant of Pioneer Butterfly Belenois aurota (Lepidoptera: Pieridae) - Chaudhary, Rajesh; Dhasmana, Vijay (Journal of the Bombay Natural History Society (JBNHS), 2025)
No Abstract.